Association of testosterone and BDNF serum levels with craving during alcohol withdrawal - Heberlein, Annemarie; Lenz, Bernd; Opfermann, Birgitt; Groschl, Michael; Janke, Eva; Stange, Katrin; Groh, Adrian; Kornhuber, Johannes; Frieling, Helge; Bleich, Stefan; Hillemacher, Thomas (Alcohol, 2016)
Preclinical and clinical studies show associations between testosterone and brain-derived neurotrophic growth factor (BDNF) serum levels. BDNF and testosterone have been independently reported to influence alcohol consumption. Therefore, we aimed to investigate a possible interplay of testosterone and BDNF contributing to alcohol dependence. Regarding possible interplay of testosterone and BDNF and the activity of the hypothalamic pituitary axis (HPA), we included cortisol serum levels in our research. We investigated testosterone and BDNF serum levels in a sample of 99 male alcohol-dependent patients during alcohol withdrawal (day 1, 7, and 14) and compared them to a healthy male control group (n = 17). The testosterone serum levels were significantly (p < 0.001) higher in the patients' group than in the control group and decreased significantly during alcohol withdrawal (p < 0.001). The decrease of testosterone serum levels during alcohol withdrawal (days 1-7) was significantly associated with the BDNF serum levels (day 1: p = 0.008). In a subgroup of patients showing high cortisol serum levels (putatively mirroring high HPA activity), we found a significant association of BDNF and testosterone as well as with alcohol craving measured by the Obsessive and Compulsive Drinking Scale (OCDS). Our data suggest a possible association of BDNF and testosterone serum levels, which may be relevant for the symptomatology of alcohol dependence. Further studies are needed to clarify our results.
EVALuna2:23779